Simulation Analysis for Big Piston of Hydraulic Bottle Jack - Roszaidi, Muhammad Harith; Wan Abdul Rahman, Wan Mohd Wardi (Progress in Engineering Application and Technology, 2023)
This study is to decide the material suit that obtained result and data for product from simulation analysis. A fully constructed Computer-Aided Drawing (CAD) for hydraulic bottle jack to run simulation, motion and costing. Result and data used to gain suit for selecting material of hydraulic bottle jack part. SolidWorks software were optimized to define the data and result. A better material that can withstand high stress, high in strength and lower cost will decided to choose. Further analysis need, can be done more in detail regarding this data gather such as analysis the perimeter, manufacturing process and using other software for analysis.